Budesonide nasal irrigations in the postoperative management of chronic rhinosinusitis. Issue 9 (17th June 2013) - Jang, David W.; Lachanas, Vasileios A.; Segel, Jamie; Kountakis, Stilianos E.
<x xml:space="preserve">Abstract</x> Background Nasal steroids play an important role in the postoperative management of patients with chronic rhinosinusitis (CRS). However, commercially available nasal steroid sprays may not deliver adequate amounts of medication to the entire postoperative sinus cavity. The off‐label use of budesonide nasal irrigation (BNI) theoretically solves this problem by delivering concentrated steroid solution through a high‐pressure, high‐volume system. Several studies have attested to the safety of BNI, but there are very few reports of its efficacy. Methods This is a retrospective review of prospectively‐collected data. We identified 60 patients who were prescribed BNI postoperatively, but had a lapse in therapy for 1 month or longer. The 20‐item Sinonasal Outcomes Test (SNOT‐20) and Lund‐Kennedy endoscopy scores while the patients were using BNI were compared with scores from the same patients while they were not using BNI. Student paired t test was used for statistical analysis. Results Thirty patients had eosinophilic chronic rhinosinusitis (eCRS) with polyps (eCRSwNP), 13 had allergic fungal sinusitis (AFS), 13 had Samter's triad (ST), and 4 had eosinophilic chronic rhinosinusitis without polyps (eCRSsNP). Mean follow‐up time was 25 months (range, 2–89 months). Overall, SNOT‐20 scores were significantly lower with BNI (p < 0.05). On subgroup analysis, SNOT‐20 scores were significantly improved with BNI for patients with eCRS and Samter's triad (p = 0.04, 0.03). Endoscopy scores were significantly improved only in the eCRS group (p = 0.02). Conclusion The addition of BNI is beneficial in the postoperative management of patients with CRS.